Personal attributes and coping processes in explaining psychosomatic symptoms in prisoners - Buško, Vesna (1997)

(untitled) (Array)
Within a framework of transactional stress and coping theory the study analyzes the determinants of inmate adjustment to imprisonment. Relevant demographic and criminological measures, and self-report instruments for the assessment of personality, i.e. dimensions of self-concept and neurotic syndrome factors, some situational features, and mediating processes - cognitive appraisals and coping, were taken in the sample of 475 males incarcerated in Croatian penal institutions. Self-report psychosomatic problems scale was administered as a short-term measure of inmate adjustment to the conditions of prison life. Relative predictive power of particular groups of individual, situational and mediating variables was estimated by hierarchical regression procedures, with the cognitive appraisal on event controllability taken as a moderator variable. With low level of perceived controllability, all groups of predictor variables accounted for significant portion of criterion variance, whereas significant additive contribution in the group with high perceived controllability was found for personality dimensions and two sets of mediating processes variables. Findings support theoretical views regarding mediating role of coping mechanisms, and the moderating role of perceived event controllability in establishing mutual relations among the components within the stress model.